Attendance Tracking and Monitoring System using Radio Frequency Identification Technology with SMS Notification - Dultiao, Jay Ar (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study developed and evaluated an Attendance Tracking and Monitoring System using Radio Frequency Identification (RFID) Technology with SMS Notification for Quirino State University to address the limitations of the existing manual attendance monitoring system, including recording inaccuracies, delayed reporting, administrative inefficiencies, and limited real-time monitoring. The study was anchored on RFID technology, SMS notification, the Feature-Driven Development (FDD) methodology, the Input–Process–Output (IPO) model, and the ISO/IEC 25010 Software Quality Standards. A descriptive-developmental research design employing qualitative and quantitative approaches was used. Qualitative data were collected through interviews to identify attendance monitoring problems, while quantitative data were gathered using an ISO/IEC 25010 standardized questionnaire to evaluate software quality. The study involved 162 purposively selected participants consisting of administrators, IT personnel, IT experts, students, and employees. Data were analyzed using thematic analysis and weighted mean. The developed system automated attendance recording, generated real-time attendance reports, maintained a centralized database, and provided SMS notifications to stakeholders. Findings showed that the system effectively addressed the operational challenges of manual attendance monitoring and achieved a Very Great Extent of compliance with the ISO/IEC 25010 Software Quality Standards in terms of functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, and portability. The study concluded that the developed system is an effective and reliable solution for improving attendance management and institutional efficiency. It recommends the adoption of the system by Quirino State University, appropriate user training, and further enhancement of the system’s functionalities for broader institutional application. The study supports Sustainable Development Goal (SDG) 4 (Quality Education), SDG 9 (Industry, Innovation and Infrastructure), and SDG 16 (Peace, Justice and Strong Institutions) by promoting digital transformation, efficient educational management, and accountable institutional processes. The system contributes to technological, educational, institutional, and socio-economic sustainability by improving operational efficiency, strengthening data management and communication, and supporting evidence-based decision-making.